The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12885-019-5620-6
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-944 overexpression is a biomarker for poor prognosis of advanced cervical cancer

Abstract: Background One-third of cervical cancer patients are still diagnosed at advanced stages. The five-year survival rate is decreased in about 50% of advanced stage cervical cancer patients worldwide, and the clinical outcomes are remarkably varied and difficult to predict. One of the miRNAs known to be associated with cancer tumorigenesis is miR-944. However, the prognostic value of miR-944 in cervical cancer has not been fully investigated. The aim of this study was to analyze clinical significance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…21,33 Numerous studies have further reported on the dual functions of miRs in carcinogenesis. [34][35][36][37] For example, miR-944 and miR-150-5p may function as oncogenes to exacerbate cervical carcinogenesis. 35,37 Inversely, miR-29a and miR-144-3p may act as tumor suppressors to inhibit invasion and metastasis of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…21,33 Numerous studies have further reported on the dual functions of miRs in carcinogenesis. [34][35][36][37] For example, miR-944 and miR-150-5p may function as oncogenes to exacerbate cervical carcinogenesis. 35,37 Inversely, miR-29a and miR-144-3p may act as tumor suppressors to inhibit invasion and metastasis of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…miR-944 was significantly higher expressed in cervical cancer tissues compared to controls, as well as in HPV-positive samples compared to those that were HPV-negative [142]. Its expression was associated with advanced FIGO stage, bulky tumor size, lymph node metastasis, and lower survival rates [142]. Considering all of the above, miR-944 could potentially serve as a prognostic biomarker [142].…”
Section: Mirnas In Cervical Cancermentioning
confidence: 99%
“…Although many studies stated that it functions as an oncogene in various malignancies, among them being cervical cancer, by stimulating cell migration, invasion and proliferation [140,141], there are some that described tumor suppressor properties in cancers located in the colon, stomach, and breast [159][160][161]. The hypothesis that it might have oncogenic functions was recently studied using five types of cell lines and 116 cervical tissues [142]. miR-944 was significantly higher expressed in cervical cancer tissues compared to controls, as well as in HPV-positive samples compared to those that were HPV-negative [142].…”
Section: Mirnas In Cervical Cancermentioning
confidence: 99%
See 2 more Smart Citations